Whatever happened to educational management? The case for reinstatement. (January 2021) - Craig, Ian
'Leadership' has now become one of the most over-used terms in school organisation, so much so that it is now difficult to find mentions of 'management' and 'administration' in school organisation literature. Papers published in Educational Management, Administration and Leadership and Management in Education over the last few years confirm this view. This article argues that although there is a significant overlap between them, leadership, management and administration are different from each other and this should be recognised when talking and writing about school organisation and development, with not all three being subsumed under the banner of 'leadership'. In particular, the article argues for the re-establishment of management as a major element in the development and training of heads and prospective heads of schools and colleges.